PROTECTING THE ENVIRONMENT — THE DUTY OF HUMANITY - A’zamjonova Sarvinoz Sarvar qizi,; Mannobov Abdumalik Mansurjon oʻgʻli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores the vital importance of protecting the natural environment in our daily lives. It examines how human activities such as deforestation, industrial pollution, and littering are causing irreversible harm to nature and, by extension, to human health. Drawing on the wisdom of great historical figures — Ibn Sino, Amir Temur, and the teachings of President Shavkat Mirziyoyev — the article argues that caring for the environment is not merely a civic duty but a deeply personal and moral responsibility. Through reflection and practical suggestions, the article calls on every individual to take small but meaningful steps toward protecting our shared planet.